Asmat Art Centre di Agats Kabupaten Asmat (Pendekatan Arsitektur Post Modern) - Henry Soleman Raubaba; Muchlis Alahudin; Theresia Avilla Gedoe (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2020)
Asmat is famous for its culture, namely wood carving and dance. There are two major events held each year in October and June. Types of activities and competitions include traditional traditional dance and statue auction demonstrations intended for adults, sculpture for the school level, socio-drama, decorative boat maneuvers and others. With the increase in activities and the number of artists every year and there is no place that can accommodate all artistic activities. so that we need a forum that becomes the center of art activities or the Asmat Art Center in Agats Asmat with a post modern architectural approach. The research method that I use is descriptive method. Data collection techniques through observation, interviews and literature study from related agencies such as the Asmat Regency Culture and Tourism Office, Asmat Regency BAPPEDA, Asmat Regency Public Works Office and other related agencies which contain data on the types of activities and the number of actors, maps and building rules. The standard building book about the museum space. The results of the design of the Asmat Art Center were designed with a post modern architectural approach, namely the combination of two modern and traditional styles of Asmat culture, namely Rumah adat Jew. Where to consider balance, esthetic and unity.